Spectral Comparison of Neutron-Irradiated Natural and Enriched Ytterbium Targets for Lu-177 Production - M. Maiyesni; S. Febriana; I. Kambali; D. Kurniasih (PPIKSN-BATAN, 2019)
Beta-emitting radioisotope 177Lu has been suggested for radioimmunotherapy, peptide receptor radionuclide therapy, or another radionuclide therapy due to its excellent properties for destroying cancer cells. In this experimental investigation, natural ytterbium (natYb) and enriched 176Yb targets were irradiated with thermal neutrons at 1.2×1014 cm-2s-1 neutron flux for 95 hours. Using a high-purity germanium (HPGe) detector-based spectroscopy system, the post-irradiated targets were measured and the produced radioisotopes were identified according to their gamma ray emissions. Experimental results indicated that several radioisotopes such as 169Yb and 175Yb dominate the post-irradiated natYb target, though a relatively weak intensity of 177Lu was also recorded. In contrast, 177Lu radioisotope dominates the gamma rays observed in the post-irradiated enriched 176Yb target following elution with HNO3 solution. For the first time, evidence is found of 175Yb impurity in the post-neutron-irradiated enriched 176Yb2O3 target as a result of 176Yb(n,2n)175Yb nuclear reaction. This work recommends future 177Lu radioisotope production using enriched 176Yb2O3 target.